Financial performance measures for Kansas swine farms, 1983-1992 - Michael R Langemeier; B M Purdy (Kansas Agricultural Experiment Station Research Reports, 1994)
Financial performance measures assist managers in making strategic plans and in tracking progress in relationship to a firm's goals. Kansas Farm Management Association data were used to compute benchmark financial performance measures for swine farms from 1983 to 1992. Annual average net farm income during the study period was 36,370 and ranged from a loss of 6,808 in 1983 to a profit of 69,418 in 1990. Return on investment ranged from -9.36% to 12.09% and averaged 3.71%over the period. The average debt to asset ratio was above 40% in every year except 1989, 1990, and 1992. The average debt to asset ratio was lower in 1992 (29 %) than in any other year of the study period.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Profitability; Liquidity; Solvency